Behavioral and demographic associations of optimal glycemic control among patients with type 2 diabetes mellitus in Sri Lanka: a multicenter study - Warsha De Zoysa; Thilak Priyantha Weerarathna; Ipitagama Liyana Arachchige Nuwan Darshana; Udari Kaushalya Egodage; Priyamali Jayasekara; Vathulan Sujanitha; Shehan Silva; Chamila Mettananda; Manoji Pathirage; Udayangani Ramadasa; Dhammika Randula Palangasinghe; Keddagoda Gamage Piyumi Wasana; et al. (BMC Endocrine Disorders)
Abstract Background Type 2 diabetes mellitus (T2DM) is an escalating global public health concern. Effective management of T2DM needs a holistic approach, considering not only the medical interventions but also demographic and behavioral factors. This multicenter study aims to investigate the association between optimal glycemic control and demographic and behavioral factors among patients with T2DM followed up in outpatient clinics of tertiary care hospitals across Sri Lanka. Methods A cross-sectional study was carried out involving T2DM patients (n = 2013) visiting outpatient clinics at seven tertiary care facilities across five provinces in Sri Lanka. Information related to sociodemographic and behavioral factors was collected using an interviewer-administered questionnaire. HbA1C < 7% was considered as optimal glycemic control. Predictors for glycemic control were identified using multiple logistic regression at a 0.05 significance level. Results Out of the total sample, 99.1% were on pharmacological treatment for T2DM while the minority were solely on dietary management. The optimal glycemic control had been achieved by 43.4%. Female gender (aOR = 1.56, 95% CI 1.18–2.05), younger age group (aOR = 1.39, 95% CI 1.06–1.82), non-Sinhalese ethnicities (aOR = 1.34, 95% CI 1.02–1.77), inadequate adherence to antidiabetic medication (aOR = 1.71, 95% CI 1.31–2.24), longer disease duration (aOR = 1.51, 95% CI 1.13–2.02), being treated with insulin (aOR = 2.79, 95% CI 1.77–4.41), and daily alcohol use (aOR = 2.27, 95% CI 1.19–4.32) were identified as risk factors for inadequate glycemic control in multiple logistic regression. Conclusion Over 50% of individuals demonstrated suboptimal glycemic control. It is recommended to implement targeted interventions for specific subgroups to address distinct demographic and behavioral factors to achieve optimal glycemic control and clinical outcomes for diabetes patients in Sri Lanka.